PRODUKSI ENZIM SELULASE TERMOSTABIL DARI BAKTERI NG2 MENGGUNAKAN BERBAGAI SUMBER SELULOSA ASAL LIMBAH PERTANIAN DAN PERKEBUNAN (Production of Thermostable Cellulase Enzyme by NG2 Bacteria Using Various Cellulose Sources from the Agriculture Waste) - Rahmad Fani Ramadhan; M. Montesqrit; Yetti Marlida (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2020)
This experiment aimed to determine the best cellulose sources from the agricultural by product on the production of the thermostable cellulase enzymes by thermophilic bacteria (NG2) and also to find out the best concentration level of the selected sources of cellulose. The experiment was conducted in two stages using a completely randomized design (CRD). In phase 1, four cellulose sources were used, namely A: corn cobs, B: rice straw, C: coconut fiber, and D: oil palm trunk, in which the replication for each source was five. In phase 2, the best sources of cellulose from the phase 1 was used at four different levels of concentration, i.e., A: 2%, B: 3%, C: 4%, and D: 5%, in which replication for each concentration was five. The result of phase 1 showed that the corn cobs was the best cellulose source in producing cellulase enzyme. This was indicated by the activity of 0.329 U/ml, the enzyme protein of 0.0328 mg/ml, and the specific activity of 10.165 U/mg, which were significantly higher (P<0.01) than those of other cellulose sources. The results of phase 2 showed that the concentration of 4% (w/v) had the highest (P<0.01) specific activity of 44.002 U/mg compared with those of the other concentrations. In conclusion, the highest production of cellulase enzyme using thermophilic bacteria (NG2) was obtained at the concentration of 4% (w/v) using the corn cobs as the cellulose source.